A sensitivity analysis of fundamental factors in relation to firms' returns in Malaysia / Mohamad Nurizzat Noh - Noh, Mohamad Nurizzat (2015)
The present work extends the evidence on the factors relevant for stock returns in Malaysia. Numerous literatures are still debating on the ability of liquidity to explain stock returns. Hence. the current study aims to analyse the company stock returns and liquidity by controlling other fundamental variables such as size and book-to-market value to define the relationship. Ten companies from five different sectors in Kuala Lumpur Stock Exchange ( KLSE ) were selected on a monthly basis from the period of 2011 to 2013. A multiple linear regressions analysis was employed to every single company and it was discovered only 30% of the sample was significant at 95% confidence level. Generally, it was found that liquidity was negatively related towards stock returns for Consumer sector and positively related for industrial sector. On the other hand, size proved to have contradictory results produced. Book-to-market value was found to be positively related towards stock returns in the Plantation sector. A comparison analysis which was carried out by positioning the companies into rank revealed that lower liquidity, larger firm's size and lower book-to-market value are able to explain the stock returns. This finding is in line with those of Chordia. Subramanyam and Anshuman (2001) for liquidity and Ban (1981) for size.